PENERAPAN MODEL PEMBELAJARAN KREATIF-PRODUKTIF DALAM PEMBELAJARAN FISIKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMA - Nurfitri, Alia (2013)
Research of implementation creative-productive learning model on physics learning to increase learning outcome of senior high school student is motivated by the low of student learning outcomes in physics. Learning physics in schools are still using the conventional method which teacher centered learning. Low optimizing of KIT management in school is also a factor of this research. Through the implementation of creative-productive learning model, the learning of physics can be expected to involve students actively in learning, it can also be an alternative solution to the problem of low optimizing KIT. Implementation of this model is try to increase student learning outcomes in physics and also can achieve the aim of physics learning which include process, product and attitude. This research use quasi-experimental research design with one group pretest-posttest design. The subjects were 36 students in one class at first grade of senior high school in Bandung, second semester of academic year 2012/2013. Increase of student learning outcomes in knowledge domain are calculated by the pretest and posttest scores. Acquisition average normalized gain is equal to 0.565 with a moderate increase in the category. While the profile of student learning outcomes in the process of science domain with an average GPA group amounted to 77.26% with the skilled category, the profile of learning outcomes in the creativity domain with an average GPA group amounted to 83.20% with skilled categories, and the profile of learning outcomes in attitudinal domian with an average GPA group amounted to 80.86% with a good category. Keywords: Creative-productive learning model, learning outcomes, taxonomy for science education Penelitian mengenai penerapan model pembelajaran kreatif-produktif dalam pembelajaran fisika untuk meningkatkan hasil belajar siswa ini dilatarbelakangi oleh rendahnya hasil belajar siswa dalam mata pelajaran fisika. Pembelajaran fisika di sekolah masih menggunakan metode konvensional yang cenderung berpusat pada guru. Pengelolaan KIT di sekolah yang kurang optimal juga menjadi salah satu faktor yang melatarbelakangi penelitian ini. Melalui penerapan model pembelajaran kreatif-produktif ini, diharapkan pembelajaran fisika dapat lebih melibatkan siswa secara aktif dalam pembelajaran, juga dapat menjadi alternatif solusi untuk masalah rendahnya optimalisasi KIT yang ada di sekolah. Sehingga pada akhirnya dapat meningkatkan hasil belajar siswa dalam pelajaran fisika, juga dapat mencapai tujuan pembelajaran fisika yang meliputi proses, produk dan sikap. Metode penelitian yang digunakan adalah metode kuasi eksperimen dengan desain penelitian One Group Pretest-Posttest Design. Subjek penelitian ini adalah siswa kelas X disalah satu SMA Negeri di kota Bandung semester genap tahun pelajaran 2012/2013 sebanyak 36 siswa. Peningkatan hasil belajar siswa pada domain pengetahuan/knowledge domain diketahui dengan menghitung skor pretes dan postes. Perolehan rata-rata gain ternormalisasi adalah sebesar 0,565 dengan kategori peningkatan sedang. Sedangkan profil hasil belajar siswa pada domain proses sains/process of science domain dengan rata-rata IPK sebesar 77,26% dengan kategori terampil, profil hasil belajar pada domain kreativitas/creativity domain dengan rata-rata IPK sebesar 83,20% dengan kategori terampil, dan profil hasil belajar pada domain sikap/attitudinal domian dengan rata-rata IPK sebesar 80,86% dengan kategori baik. Kata kunci : Model pembelajaran kreatif-produktif, hasil belajar, taksonomi untuk pendidikan sains(taxonomy for science education)